Demonstration of boron arsenide heterojunctions: A radiation hard wide band gap semiconductor device - Gong, Y.; Tapajna, M.; Bakalova, S.; Zhang, Y.; Edgar, James H.; Zhang, Y.; Dudley, M.; Hopkins, M.; Kuball, M. (My University, 2010)
B12As2/SiC pn heterojunction diodes based on the radiation-hard B12As2 deposited on (0001) n-type 4H–SiC via chemical vapor deposition were demonstrated. The diodes exhibit good rectifying behavior with an ideality factor of 1.8 and a leakage current as low as 9.4×10−6 A/cm2. Capacitance-voltage measurements using a two-frequency technique showed a hole concentration of ∼1.8–2.0×1017 cm−3 in B12As2 with a slight increase near the interface due to the presence of an interfacial layer to accommodate lattice mismatch. Band offsets between the B12As2 and SiC were estimated to be ∼1.06 eV and 1.12 eV for conduction band and valance band, respectively. The authors gratefully acknowledge the support by the Engineering and Physical Science Research Council (EPSRC) under Grant No. EP/D075033/1, by the National Science Foundation Materials World Network Program under Grant No. 0602875 under the NSF-EPSRC Joint Materials Program, and by the U.S. Department of Energy under Contract No. DE-AC02-98CH10886.
Keywords: Rich Solids; Capacitance; Irradiation; Growth